Comparative Study of Generalized Sum Graphs via Degree-Based Topological Indices. (14th February 2022) - Javaid, Muhammad; Javed, Saira; Bonyah, Ebenezer
Abstract : In theoretical chemistry, topological indices (TIs) have important role to predict various physical and structural properties of the study under molecular graphs. Among all topological indices, Zagreb-type indices have been used more effectively in the chemical literature. In this paper, we have computed first Zagreb, second Zagreb, forgotten, and hyper Zagreb indices of the generalized Q -sum graph H 1 Q α H 2 in the form of different TIs of its basic graphs, where α ≥ 1 is a positive integer. This family of graphs is obtained by the lexicographic product of the graph Q α H 1 and H 2, where Q α H 1 is constructed with the help of the generalized line superposition operation Q α on H 1 . As a conclusion, we also checked the correlation between predefined graph H 1 H 2 under the operation of lexicographic product H 1 and H 2 with newly defined generalized Q -sum graphs H 1 Q α H 2 using linear regression models of various degree-based TIs.